Tawar Kampung an Instrument of Social Control in Gayo Lues Society: A Study of the Sociology of Islamic Law - Ripi Hamdani; Nufiar Nufiar; Ahmad Syahyana (Islamic Studies and Civilization Journal, 2025)
This study raises the issue of the complexity of social control in Aceh Province, particularly through the Tawar Kampung tradition in Gayo Lues, which is often viewed merely as a cultural practice without an integrative analysis of Islamic law. The urgency of this research lies in the need for a deeper understanding of informal social control mechanisms capable of maintaining communal harmony when the formal legal system has limitations. This study aims to analyze the sociological function of Tawar Kampung and examine its normative position from the perspective of the sociology of Islamic law through the framework of 'urf and maqāṣid al-syarī'ah. Using a qualitative method with a literature study design and a normative-sociological approach, data are analyzed through a hermeneutic circle to achieve a holistic understanding. The research findings indicate that Tawar Kampung functions as an effective instrument of restorative justice because it is supported by the moral legitimacy of traditional leaders (Sarak Opat) and the internalization of collective values. Normatively, this practice is classified as 'Urf ṣaḥīḥ because it aligns with the principles of sharia in preserving religion and lineage and preventing social damage. In conclusion, Tawar Kampung is a manifestation of living law that is able to synergize local wisdom with the flexibility of Islamic law to realize substantive public welfare.